Improving Cadres' Knowledge and Skills through Isotonic Movement Training in Reducing Joint Pain and Stiffness in the Elderly - Fauzia, Wilda; Syaefudin, Achmad; Haji, Son; Aditya Putri, Arista (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Joint pain and stiffness is one of the complaints of joint disorders that are generally experienced by the elderly (elderly). If left unchecked over time, it will result in disability and functional impairment in daily activities. Therapy to reduce complaints can be in the form of giving pain medication and without giving drugs with joint motion exercises. Isotonic movements can help reduce joint pain and stiffness. The role of cadres in supporting the prevention of joint disorders is important. This activity is called isotonic movement training to reduce joint pain and stiffness in the elderly. The target of the training was 21 elderly posyandu cadres. The methods used in providing training are lectures, practices and discussions. The purpose of the training is to increase cadres' knowledge of isotonic exercises and improve cadres' basic skills about isotonic exercises. After the training, the knowledge and skills of cadres increased. Isotonic movement exercises can help reduce joint pain and stiffness in the elderly.